PENGGUNAAN MHEALTH PADA PASIEN PASCA RAWAT INAP PENYAKIT KRONIS: LITERATURE REVIEW - Anggy Febiarthy; Evi Martha (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2023)
Chronic non-communicable diseases (NCDs) are a persistent global health problem. Patients with chronic medical conditions often experience difficulties in self-management of their disease, especially after discharge from the hospital. The gap in information and the patient's ability to maintain and improve their health after hospitalization is challenging. One of the efforts to manage chronic diseases for post-hospitalization patients is using mobile health technology (mHealth). This study aimed to determine the benefits and challenges of using mHealth in the self-management of chronic diseases in post-hospitalization patients. The method used is the literature review of article searches on electronic databases, namely Proquest, Scopus and Pubmed, with publication years 2019-2023. The review of 7 selected articles shows that using mHealth in post-hospitalization patients with chronic diseases can facilitate patient behavior change and interaction with health workers. It also can potentially reduce patient readmissions and the cost of care. The challenges in using mHealth in post-hospitalization patients with chronic diseases are low compliance due to loss of interest, discomfort when using the device, fatigue, socioeconomic status, and patient culture. The option of creating mHealth using gamification strategies to increase intrinsic motivation should be considered, but recommendations on the components of fun, personalization, performance feedback and safety are also important. Therefore, it is important to assess patient preferences, the involvement of healthcare professionals and mHealth designers, and communication campaigns that emphasize exchanging reliable and correct information.